Clockwork angels [compact disc, unabridged] - Anderson, Kevin J., 1962- (Brilliance Audio, 2012)
Friend and major Rush fan Kevin Anderson has spent the last two years working with the band to tell the story their album tells in prose novel form. The story is a young man's quest to follow his dreams, as he travels across a lavish and colorful world of steampunk and alchemy, with lost cities, pirates, anarchists, exotic carnivals, and a rigid Watchmaker who imposes precision on every aspect of life.